Impact of Sintering Temperature on Silica Water Filter Fabricated via Cold Isostatic Pressing - Tuan Nidzan, Tuan Nur Azleen Amira; Ahmad, Sufizar; Muhammad Syahmie Sufi Abdul Shukor (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study investigates the effect of sintering temperature on the properties and performance of silica water filters fabricated using the Cold Isostatic Pressing (CIP) method. Silica samples were compacted using CIP and sintered at three temperatures: 1000°C, 1100°C, and 1200°C. Scanning Electron Microscopy (SEM) was used to observe the microstructure and grain bonding. Physical properties such as porosity, density, shrinkage, and water absorption were evaluated to understand the influence of sintering conditions. Filtration performance tests were conducted to assess the efficiency of each sample. The findings aim to identify the optimal sintering temperature for producing high-performance silica water filters with improved structural integrity and filtration efficiency.